Kaarina Aitamurto, Scott Simpson, Modern Pagan and Native Faith Movements in Central and Eastern Europe - Schaab, Philipp (Zeitschrift für junge Religionswissenschaft, 2014)
Rezensiertes Werk: Kaarina Aitamurto, Scott Simpson, Modern Pagan and Native Faith Movements in Central and Eastern Europe. Acumen Pub, Durham, 2013, 352 S., ca. 87,45 € ISBN: 978-1-84465-662-2